A coordenação pedagógica e a práxis educativa na escola - Rudnick, Marilda da Silva (2014)
This research is linked to the Graduate Program in Education, (PPGEDU / CUR / UFMT) in Teacher Training and Educational row and Public Policy aims to examine how education professionals realize the pedagogical work of the coordinating education in a school state high school, through the testimonies of teachers, coordinators, director, technical – administrative and support staff, about the role of relevant pedagogical coordination at school functions. Based on the main objective, the conduct of the research agenda on the following objectives: a) To investigate how the intrinsic understandings about education, present in the discourse of professional education permeate the perception about the role of teaching coordination b) Understand how are structured and articulated the functions of pedagogical Coordination in school, what is normative and what the respondents expect c) analyze the structures and joints of the pedagogical coordinator for assistance in the continuing education of professionals in education and how it is perceived by education professionals. Based on the considerations made, the questions concern exactly the repercussions in everyday school life, the actions that the pedagogical coordinator plays (according to their functions ) is effective. Thus, the research question: How education professionals perceive the work of coordinating education in the school routine? The choice of methodological approach of qualitative research dialectical character is justified by the fact that analyzes establish dialogue between the methodology, theoretical framework and the data collected. The instruments to collect data selected are: observation, memorials training, the semi-structured interviews and documentary analysis. The locus of research is a secondary school of the statewide network of Primavera do Leste - MT. Home study discussing education as a human phenomenon, commitment to the world for it is necessary to understand that education makes sense only if it is guided in the debate, in the consciousness of rights and duties. Then I wonder about the school as a space for knowledge building and learning to live together. In this sense, the school teaching coordination is considered as coordinator for the realization of the dream of a fairer education and denouncing the exploitation while utopian to organize pedagogical practice at school and coordinate the pedagogical work doing the educational praxis in school having as a point of departure and arrival in the classroom. Continuing education for the teaching coordination to succeed in its purpose and need for an ongoing process occurring changes and transformations of their own practice, dialogical, with the theory. Finally realize the considerations on search results. The dissertation is grounded from the theoretical framework of critical pedagogy embodied in educational thought of Freire, Gadotti, Veiga Ferreira and others.